Protective effects of quercetin against glyphosate-induced nephrotoxicity in rats: role of oxidative stress, inflammatory response, and apoptotic pathways - Albrakati, Ashraf (Frontiers in Veterinary Science, 2025)
BackgroundGlyphosate, the most widely used herbicide globally, accumulates in renal tissue causing kidney damage through incompletely understood mechanisms. This study evaluated quercetin’s nephroprotective effect against glyphosate-induced kidney injury in rats.MethodsFive groups of male Wistar rats (n = 10 each) received daily treatments for 21 days: control, glyphosate (25 mg/kg), quercetin (50 mg/kg), and quercetin+glyphosate at low (25 mg/kg) or high (50 mg/kg) doses. All treatments were administered by oral gavage for 21 days. Renal parameters, oxidative stress markers, inflammatory mediators, and apoptotic indicators were assessed using spectrophotometric assays, ELISA, qRT-PCR, and histology.ResultsGlyphosate impaired renal function, increased kidney weight, and elevated kidney injury molecule-1 (KIM-1) levels. It suppressed antioxidant enzymes (CAT, SOD, GPX) and downregulated their mRNA expression (Cat, Sod2, and Gpx-1, respectively), while depleting GSH and increasing oxidative markers (MDA, NO). Notably, glyphosate reduced Nrf2 protein and Nfe2l2 gene expression, disrupting this master regulator of antioxidant responses, with concurrent Hmox-1 downregulation. Glyphosate upregulated pro-inflammatory cytokines (TNF-α, IL-1β, IL-6), increased TLR-4 and NOS2 expression, activated mitochondrial apoptosis by increasing pro-apoptotic proteins (BAX, CYTOCHROME C, and CASPASE-3) while decreasing anti-apoptotic BCL-2 protein levels, with corresponding changes in gene expression. Consistent with protein findings, Bcl-2 gene expression was significantly downregulated, further confirming the shift toward pro-apoptotic signaling. Quercetin dose-dependently attenuated these alterations, with high-dose providing superior protection compared to low-dose by restoring gene expression and enzyme activities. Histopathological examination confirmed quercetin mitigated glyphosate-induced tubular degeneration and glomerular atrophy.ConclusionQuercetin protects against glyphosate nephrotoxicity through antioxidative, anti-inflammatory, and anti-apoptotic mechanisms, suggesting therapeutic potential against herbicide-induced kidney injury.